2019
DOI: 10.1002/ajoc.201900154
|View full text |Cite
|
Sign up to set email alerts
|

Acid Activation and Chemical Oxidation in the Synthesis of meso‐Tetraphenylporphyrin using a Mixed‐Solvent System

Abstract: The specific roles of solvents in the synthesis of meso-tetraphenylporphyrin (TPP) using a classical mixedsolvent of acetic acid, propionic acid, and nitrobenzene are unclear to date. In this work, we explored the acid-activation process between benzaldehyde and pyrrole using DFT calculations. The catalytic role of carboxylic acids was proven by the formation of a carbocation intermediate. Moreover, the oxidation behavior of nitrobenzene or its analogs was studied by UV/Vis spectroscopy. In particular, the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Nitrobenzene is an indispensable raw material, which can highly be employed in producing a variety of chemical products. More specifically, compelling reasons for selecting nitrobenzene as the oxidant in this novel route for the synthesis of azobenzene are pointed out in the following (53–73):…”
Section: Resultsmentioning
confidence: 99%
“…Nitrobenzene is an indispensable raw material, which can highly be employed in producing a variety of chemical products. More specifically, compelling reasons for selecting nitrobenzene as the oxidant in this novel route for the synthesis of azobenzene are pointed out in the following (53–73):…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the acidity (p K a ) of the medium and the nature of acid catalyst (organic acid, Lewis acid) are crucial for the efficient cyclotetramerization of pyrrole with aldehyde [ 102 ]. In order to reveal the specific role of acid catalysis in combination with chemical oxidation of intermediate products, Sun et al [ 103 ] found that the most effective acid activation of the starting compounds is achieved in a mixture of propionic and acetic acids using nitrobenzene or its derivatives to oxidize intermediate porphyrinogen [ 104 106 ]. Highly pure meso -tetraphenylporphyrin was thus obtained in 38% yield in the presence of m -nitrotoluene [ 103 ].…”
Section: Principal Methodologies Of the Synthesis Of Tetrapyrrole Mac...mentioning
confidence: 99%
“…In order to reveal the specific role of acid catalysis in combination with chemical oxidation of intermediate products, Sun et al [ 103 ] found that the most effective acid activation of the starting compounds is achieved in a mixture of propionic and acetic acids using nitrobenzene or its derivatives to oxidize intermediate porphyrinogen [ 104 106 ]. Highly pure meso -tetraphenylporphyrin was thus obtained in 38% yield in the presence of m -nitrotoluene [ 103 ]. Furthermore, other nitrobenzene derivatives proved to be good oxidants providing more than 30% yield of tetraarylporphyrins containing no chlorin impurity [ 103 ] (Table 1 ).…”
Section: Principal Methodologies Of the Synthesis Of Tetrapyrrole Mac...mentioning
confidence: 99%
See 1 more Smart Citation
“…Under the inert atmosphere of nitrogen gas, they achieved the final TPP product with a yield of up to ~38% from the nominally pure to fairly pure form. The mixed solvent used for this was m-nitrotoulene, DMSO, and nitrobenzene as oxidants along with the acid catalyst 12,13 . Diane F. Marsh & et al, extended this study and prepared metalloporphyrins, e.g.…”
Section: Introductionmentioning
confidence: 99%